Tingkat Pendapatan, Metode Pengasuhan, Riwayat Penyakit Infeksi dan Risiko Kejadian Stunting di Kota Samarinda - Tanti Asrianti Naim; Nurul Afiah; Dwi Muliyana; Risva Risva (Jurnal Nasional Ilmu Kesehatan, 2019)
Nutritional problems in Indonesia, especially in children are still quite high. Nutritional problem in children including stunting with high proportion of 37,2%. This was an observational analytical study with a retrospective method to determine the risk of stunting in underfive years old children (toddler) based on the level of family income, parenting method, and history of infectious diseases in children on the working area of Juanda Public Health Center Samarinda, 2018. The population in this study was toddlers on the working area of Juanda Public Health Center Samarinda with 99 respondents consisting of 33 cases and 66 controls. The results showed that families with lower to middle income levels had a four times greater risk of stunting compare to middle to upper income level families (OR: 3,877; 95%CI: 1,329-11,310). The parenting method and history of infectious diseases did not show a significant relationship with the incidence of stunting in this research. Further research is needed to investigate other factors for stunting, include environmental factors